Strategi Pemasaran Kreatif Yang Diterapkan Di PT. Otomoto Manado Town Square - Sangkay, Reymond (JURNAL RISET BISNIS DAN MANAJEMEN, 2017)
The purpose of this research is to analyze marketing strategies creative applied in pt otomoto manado town square. The research results show that the utilization of social media to promote using the strategies marketing creative, which refers on the application marketing entrepreneurial consisting of marketing guerrilla, buzz marketing and viral marketing is the goal to introduce products and services available in PT. Otomoto manado twon square. Social media is expected to be a media promotion potential in convey a message persuasive to customers and interweave proximity personally, to achieve the purpose company.Keywords: Marketing strategy, Creativity, Otomoto Manado Town SquareÂ